Strengthening intensive care training in response to COVID-19: lessons for medical education - Mochamat Helmi; Djayanti Sari; Yenny Sulistyowati; Andreasta Meliala; Tjahja Nurrobi; Tugas Ratmono; Laksono Trisnantoro (Intelektual Pustaka Media Utama, 2026)
Frequent updates to clinical guidelines during the COVID-19 pandemic have posed significant challenges for audit processes, quality improvement, and the preparedness of healthcare professionals, particularly in intensive care settings. This study aimed to explore the impact of COVID-19-related demands on medical education and training from the perspective of healthcare teams working in intensive care units (ICUs) in Indonesia during the first wave of the pandemic. A qualitative design was employed using semi-structured interviews and focus group discussions with medical personnel directly involved in the care of COVID-19 patients at national referral hospitals. Purposive sampling was applied to recruit participants, including general practitioners, interns, residents, anesthesiologists, and ICU consultants. A total of 66 participants were included across eight focus group discussions, each consisting of eight to nine participants. Data collection continued until thematic saturation was achieved. Transcripts were analyzed using content analysis to identify key themes and subthemes. The analysis revealed five major themes: i) the need for continuous upgrading of knowledge and competencies, ii) the importance of innovative education and training approaches, iii) the role of professional organizations, iv) challenges encountered during training implementation, and v) time constraints. These findings highlight the urgent need for adaptive, continuous, and technology-supported training strategies to strengthen intensive care workforce preparedness during public health emergencies.